2022
DOI: 10.1111/1758-2229.13113
|View full text |Cite
|
Sign up to set email alerts
|

A genome–proteome‐based approach for xylan degradation by Cohnella sp. AR92

Abstract: Several members of Cohnella genus have been reported as xylanolytic bacteria with significant capacity as carbohydrate-active enzyme producers (CAZymes), whose mechanisms involving xylan degradation are a key goal for suitable applications in bio-based industries. Using Cohnella sp. AR92 bacterium, we ensembled a genomic-proteomic approach to assess plant biomass conversion targeting its xylanolytic set of enzymes. Also, the genomic traits of the strain AR92 were compared to other Cohnella spp., showing a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As can be seen in the dendrogram of enzymatic activities, the microorganisms that had the highest values of xylanolytic activity (>50%) were more frequently associated with high cellulolytic activity (70-100%), and they exhibited lipolytic activity to a lesser extent (Figure 3A and Supplementary Data S3). It has been reported that both xylanases and cellulases can be induced by the same substrates, resulting in the simultaneous expression of both proteins, maximizing degradation and assimilation in the complex lignocellulosic biomass [41]. This has also been reported in cases of microbial communities, either in autochthonous niches or in defined co-cultures [42].…”
Section: Enzymatic Activities Of Isolated Microorganismsmentioning
confidence: 82%
See 1 more Smart Citation
“…As can be seen in the dendrogram of enzymatic activities, the microorganisms that had the highest values of xylanolytic activity (>50%) were more frequently associated with high cellulolytic activity (70-100%), and they exhibited lipolytic activity to a lesser extent (Figure 3A and Supplementary Data S3). It has been reported that both xylanases and cellulases can be induced by the same substrates, resulting in the simultaneous expression of both proteins, maximizing degradation and assimilation in the complex lignocellulosic biomass [41]. This has also been reported in cases of microbial communities, either in autochthonous niches or in defined co-cultures [42].…”
Section: Enzymatic Activities Of Isolated Microorganismsmentioning
confidence: 82%
“…There were no isolated microorganisms with important productions of various enzymatic activities. In most of the evaluated substrates, when an isolate presented high values of catalytic activity, at the same time, it showed poor or no activity against other polymers, except for xylanolytic microorganisms, which present high cellulolytic activity [41]. Based on these results, there was not an enzymatic "superproducer" microorganism in the samples analysed, but in the microbial community, there was a marked "enzymatic work specialization", where the degradations of the different substrates were differentiated between species and even between genera.…”
Section: Enzymatic Activities Of Isolated Microorganismsmentioning
confidence: 99%